Kontroversi Kewenangan Pengadilan Negeri Dan Pengadilan Agama Dalam Menyelesaikan Sengketa Perbankan Syari’ah Di Indonesia - Hervina, Hervina (IAIN Samarinda, 2014)
Since the amendment of Law No. 7 of 1989 to Law No. 3 of 2006 concerning the Religious Courts, the Religious Courts increasingly expand its jurisdiction not only over disputes about the Islamic family law, but also to resolve disputes on Syari`ah economy including Syari`ah banking. The jurisdiction of the Courts to resolve the Syariah economy disputes, however, is reduced with the enactment of Law No. 21 of 2008 concerning Sharia Banking. The explanation of Article 55 paragraph (2) authorizes the District Court (Pengadilan Negeri) to resolve the Syari'ah economy disputes. This provision would cause dualism of authority and, thus, legal uncertainty as the litigants may settle their Syariah economy disputes either to the Religious Courts or the District Court.